Increase of glial molecular markers in the brain of diabetic rats reversed with vitamin E - Nedzvetsky, V; Kirichenko, S; Baydas, G (Wiley-Liss, 2003)
[Abstract Not Available]
6th European Meeting on Glial Cell Function in Health and Disease -- SEP 03-06, 2003 -- BERLIN, GERMANY